A recent study of the structural properties between of Mn-Zn-Fe2O4 and Mn-Zn-Fe2O4 /TiO2 nanocomposite (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In order for the nanomaterials to be utilized, it is vital to be able to control the structural properties of the Mn-Zn-ferrites nanoparticles (NPs) by sol-gel and Mn-Zn-ferrites /TiO2 nanocomposite (NC) generated by sol – gel method at 650, 750, and 850 oC. An examination into the possibility of producing the Mn-Zn-ferrites by sol-gel and Mn-Znferrites /TiO2 (NC) as prospective structure-tunable nanomaterials is described in this report. X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), and Fourier-transform infrared (FTIR) spectroscopy were used to characterize the structural properties of the Mn-Zn-ferrites by sol-gel and Mn-Zn-ferrites /TiO2 (NC). They were 27 to 30 nm in size with a cubic structure, while the Mn-Zn-ferrites /TiO2 (NC) were 10 to 30 nm in size with a cubic structure. FE-SEM images showed the synthesized the Mn-Zn-ferrites and the Mn-Zn-ferrites /TiO2 (NC) had a nanoparticlelike structure with a particle size of 27.77, to 72.04 nm. The strong FT-IR absorption peaks at 500 and 600 cm-1 represented an Fe-O, Mn-O, and Zn-O vibration band and 1667 cm-1 represented an TiO2 for the Mn-Zn-ferrites and the Mn-Zn-ferrites /TiO2 (NC), respectively.